Genetic variability is unrelated to growth and parasite infestation in natural populations of the European eel ( Anguilla anguilla ) - Pujolar, Jose M.; Bevacqua, Danièle; Capoccioni, Fabrizio; Ciccotti, Eleonora; De Leo, Giulio Alessandro; Zane, Lorenzo (Molecular Ecology, 2009)
International audience Positive correlations between individual genetic heterozygosity and fitness-related traits (HFCs) have been observed in organisms as diverse as plants, marine bivalves, fish or mammals. HFCs are not universal and the strength and stability of HFCs seem to be variable across species, populations and ages. We analysed the relationship between individual genetic variability and two different estimators of fitness in natural samples of European eel, growth rate (using back-calculated length-at-age 1, 2 and 3) and parasite infestation by the swimbladder nematode Anguillicola crassus . Despite using a large data set of 22 expressed sequence tags-derived microsatellite loci and a large sample size of 346 individuals, no heterozygote advantage was observed in terms of growth rate or parasite load. The lack of association was evidenced by (i) nonsignificant global HFCs, (ii) a Multivariate General Linear Model showing no effect of heterozygosity on fitness components, (iii) single-locus analysis showing a lower number of significant tests than the expected false discovery rate, (iv) sign tests showing only a significant departure from expectations at one component, and, (v) a random distribution of significant single-locus HFCs that was not consistent across fitness components or sampling sites. This contrasts with the positive association observed in farmed eels in a previous study using allozymes, which can be explained by the nature of the markers used, with the allozyme study including many loci involved in metabolic energy pathways, while the expressed sequence tags-linked microsatellites might be located in genes or in the proximity of genes uncoupled with metabolism ⁄ growth.